CHANGING LAND TRAJECTORIES: A CASE STUDY FROM INDIA USING A REMOTE SENSING BASED APPROACH. - Chadrashekhar Azad VISHWAKARMA; Somnath THAKUR; Praveen Kumar RAI; Vikas KAMAL; Saumitra MUKHERJEE (European Journal of Geography)
The change in land use land cover (LULC) pattern is the result of natural and socio-economic factors and their use by human being over time and space. Change analysis plays an important role in natural resource management and in the assessment of environmental change. Land use land cover changes over a period of 25 years have been studied with the help of remote sensing and GIS in a part of Sonbhadra district of Uttar Pradesh and Singaruli region of Madhya Pradesh. The study area situated is situated in the vicinity of Govind Ballabh Pant Sagar reservoir. The present study is focused on the changing land use practices and their implications in the study area. Land use and land cover patterns at different time viz. 1991, 2000 and 2014 were analyzed and compared using a hybrid method of classification in ERDAS Imagine version-14. Data for this purpose was sourced from remote sensing satellite imageries of LANDSAT (TM of 1991 & ETM+ of 2000 & 2014) and Survey of India (SOI) topographic sheets on 1:50000 scale. After downloading Landsat data it has been proceed and further analyzed in Arc GIS version- 10.3. In this method, a statistics of area change in agriculture, barren land and forest cover, which is governed by variation in geology and prevailing structural anomaly were calculated.